2018
DOI: 10.14505//jarle.v8.8(30).34
|View full text |Cite
|
Sign up to set email alerts
|

Current Trends in the Financial Market Development

Abstract: The paper shows that the modern tendencies of financial market based on the possibility of stratification and infrastructural development of the economy as a whole. The authors found that special attention should be given to development of infrastructural support from the state, and the formation of technological trends in the structure of public consumption. The article indicates that financial market conditions are set on the basis of the calculation of both financial and investment risks, which facili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The data for the last two countries deserve special attention. It was identified that the most significant incentive for the development of crowdfunding in the UK was the considerable tax remissions on the part of the state (Zatsarinnyi et al, 2017). At the legislative level, the UK provides tax support to relatively young funded companies that receive investment aid for high-tech developments.…”
Section: Resultsmentioning
confidence: 99%
“…The data for the last two countries deserve special attention. It was identified that the most significant incentive for the development of crowdfunding in the UK was the considerable tax remissions on the part of the state (Zatsarinnyi et al, 2017). At the legislative level, the UK provides tax support to relatively young funded companies that receive investment aid for high-tech developments.…”
Section: Resultsmentioning
confidence: 99%
“…It should have an expanded purpose for the sectors of the national economy that are implemented by the concept of sustainable development [35]. Changing socio-economic formation and the introduction of market relations in the world have necessitated the transformation of the institutional environment in the process of agrarian reform [36].…”
Section: Methodsmentioning
confidence: 99%
“…"EcoIslamicBank" is the first bank in Kyrgyzstan, which began to provide a full range of financial services, which were based on the principles of Sharia. To date, a wide network of 110 subdivisions has been created throughout the republic (Kovalenko et al, 2019;Zatsarinnyi et al, 2018). The client base of the studied bank is more than 100000 clients, the bank offers a variety of services for Islamic deposits, financing, servicing bank cards, halal transfers and much more (Voronkova et al, 2019).…”
Section: Materials and Metodsmentioning
confidence: 99%